2009
DOI: 10.1111/j.1440-1746.2009.05845.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of acidified 14C‐urea capsule breath test during pantoprazole and ranitidine treatment

Abstract: The use of acidified 14C-urea capsule did not prevent false negative UBT results in patients taking pantoprazole and ranitidine, and the duration of medication does not affect the test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Because PPI drugs have antimicrobial properties, while converting the stomach into an alkaline and hostile environment for Hp growth, the bacterial load decreases, especially in the antrum, contributing easily to false-negative results of the UBT, in contrast to serology (Hp IgG or IgA antibodies), which remains unaffected in those taking PPI medication. Most of these studies in patients taking PPIs have been carried out with UBT and showed a 10-40% falsenegative rate (14,20). In addition to PPI treatment (14-16), H 2 -blockers may also give false-negative UBT results, albeit to a lesser extent than PPI medication (12,21).…”
Section: The Ubtmentioning
confidence: 99%
“…Because PPI drugs have antimicrobial properties, while converting the stomach into an alkaline and hostile environment for Hp growth, the bacterial load decreases, especially in the antrum, contributing easily to false-negative results of the UBT, in contrast to serology (Hp IgG or IgA antibodies), which remains unaffected in those taking PPI medication. Most of these studies in patients taking PPIs have been carried out with UBT and showed a 10-40% falsenegative rate (14,20). In addition to PPI treatment (14-16), H 2 -blockers may also give false-negative UBT results, albeit to a lesser extent than PPI medication (12,21).…”
Section: The Ubtmentioning
confidence: 99%
“…False negative results, therefore, are a limitation in the use of the standard UBT in patients on PPIs. Up to 40% of individuals taking PPIs had a false negative test result[ 5 , 6 , 19 - 22 ]. While 5 d on a PPI had no significant effect on H. pylori and the UBT, one-third of volunteers had a negative UBT after being on PPI therapy for 7 d (omeprazole 20 mg )[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To maintain a low gastric pH, we used high dose citric acid, which also delays gastric emptying [14]. However, others have hypothesized that these two factors appear unlikely to be the critical determinants in the increased access of urea to the urease enzyme in vivo [15-17]. …”
Section: Discussionmentioning
confidence: 99%